MECHANISMS FOR DEVELOPING CIVIC AWARENESS AND POLITICAL PARTICIPATION OF YOUTH - Orinbetov, Nietulla Turdimuratovich (SCIENCE and SOCIETY, 2026)
This article analyzes the mechanisms for developing civic awareness and political participation among youth. It examines youth participation in social and state life, the development of legal consciousness and responsibility, as well as normative-legal and practical approaches. The study discusses opportunities to enhance civic awareness and political activity through education, public engagement, NGOs, and media. The findings indicate that fostering civic responsibility among youth is a crucial factor in strengthening a democratic society.
Keywords: youth; civic awareness; political participation; civic responsibility; state youth policy; democratic society